PENGARUH PANDEMI COVID-19 TERHADAP EKSISTENSI BISNIS UMKM DALAM MEMPERTAHANKAN BUSINESS CONTINUITY MANAGEMENT (BCM) - Anngit Dyah Kusumastuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to analyze the impact of the Covid-19 pandemic on the existence of MSME business in business continuity management (BCM). The research methods used is descriptive qualitative method based on secondary data from research result and reference on data and information from journals and online reporting. The result showed that the impact of the Covid-19 pandemic was felt directly by the sustainability of the MSME business in decreasing its productivity. The business sector that wass constrained by its development and even experienced a decline during the Covid-19 pandemic was the transportation, tourism, shopping center, and offline trade business which only focused direct consumer visits. While business activities that can still survive and exist to serve consumers (transformed using an online application platform) are education, retail, staple food.